Reframing Community Empowerment through Creativepreneurship as a Multidisciplinary Social Service Model - Novi Fitria Hermiati; Muhtarom Muhtarom; Mohd Faiz Hilmi; Lukita Pasha; Lakshmi Devi (ADI Pengabdian Kepada Masyarakat, 2026)
Community empowerment through creativepreneurship is essential for sustaining the quality of life and economic self-reliance of local communities, yet the implementation of effective multidisciplinary social service models remains limited. This article aims to evaluate the reframing of community empowerment through creativepreneurship as a multidisciplinary social service model that can enhance community participation and capacity building. The community service approach used a participatory method involving structured training, direct mentoring, interviews, and observation on 47 local MSME participants over six months. Data analysis was conducted through source triangulation to ensure the validity of the findings. Service outcomes showed an increase in creative entrepreneurial skills, strengthened cross-sector collaboration, and improved productivity of micro enterprises. Participants reported increased engagement in local economic activities and the application of innovative ideas in products and marketing. The multidisciplinary social service model based on creativepreneurship is effective in strengthening community empowerment, improving UMKM competencies, and reinforcing socio-economic networks within the community. Recommendations for future research include enhancing digital marketing strategies and expanding the scale of training to other social groups.